mSphere of Influence: How the single cell contributes to the collective - Gina R. Lewin (mSphere, 2025)
ABSTRACT Gina Lewin works in the field of microbial ecology, with a focus on the human microbiota. In this mSphere of Influence article, she reflects on how two papers describing bacterial single-cell RNA-seq—“Prokaryotic single-cell RNA sequencing by in situ combinatorial indexing” by S. B. Blattman, W. Jiang, P. Oikonomou, and S. Tavazoie (Nat Microbiol 5:1192–1201, 2020, https://doi.org/10.1038/s41564-020-0729-6) and “Microbial single-cell RNA sequencing by split-pool barcoding” by A. Kuchina, L. M. Brettner, L. Paleologu, C. M. Roco, et al. (Science 371:eaba5257, 2021, https://doi.org/10.1126/science.aba5257)—impacted her work by developing a new approach to study how single cells of bacteria contribute to ecosystem-level processes.